Land Suitability and Capability For Mariculture Utilization of Coastal Area of Manado Tua Island - Adnan S. Wantasen; Wilmy. E. Pelle; Alex D. Kambey (Jurnal Ilmiah PLATAX, 2020)
The concept of land suitability and carrying capacity in utilizing the coastal land area of Manado Tua Island is a long-term goal in the study of sustainable coastal and small island management. Meanwhile, alternative livelihoods for sustainable aquaculture food sources are a special target. The potential of freshwater supply becomes a limiting factor for small islands, in addition to land availability. The special objective is the use of aquatic land as aquaculture land which has an impact on alternative livelihoods and the availability of food sources. The land suitability analysis is carried out in the following stages: (1) preparing a map of the Manado Tua Island area, (2) creating a matrix for the suitability of aquaculture activities, (3) providing weighting and scoring, and (4) conducting spatial analysis. The biogeophysical conditions of the coastal waters of Manado Tua Island are classified as normal for mariculture cultivation activities. Geographically the island is located at coordinates 01Âº 37 '57 "North Latitude and 124Âº 41" 56 "East Longitude. The very suitable location I was 44.03 m2, while the suitable land was 34.25 m2, and the conditionally suitable land was 17.13 m2. For location II, the area that fully meets the requirements is 70.50 m2, and those that meet the appropriate requirements are 49.86 m2, and those that meet the conditionally are 27.51 m2. The land area of Manado Tua Island is 1,056.02 ha. The condition of freshwater sources has not yet the potential to meet the needs of the community and visiting tourists.Keywords: land suitability, aquaculture, freshwater utilization, Manado Tua IslandAbstrakKonsep kesesuaian lahan dan daya dukung dalam memanfaatkan areal lahan pesisirÂ  Pulau Manado Tua merupakan tujuan jangka panjang dalam studi pengelolaan pesisir dan pulau kecil secara berkelanjutan. Sedangkan alternatif mata pencaharian untuk sumber pangan hasil budidaya perairan secara berkelanjutan menjadi target khusus. Potensi sediaan air tawar menjadi faktor pembatas pulau kecil, disamping ketersediaan lahan. Adapun tujuan khusus adalah pemanfaatan lahan perairan sebagai lahan budidaya perikanan yang berdampak pada alternatif mata pencaharian serta ketersediaan sumber bahan pangan. Analisis kesesuian lahan dilakukan dalam tahapan: (1) penyusunan peta kawasan Pulau Manado Tua, (2) membuat matriks kesesuaian kegiatan budidaya perikanan, (3) memberikan pembobotan dan pengharkatan, dan (4) melakukan analisis spasial. Kondisi biogeofisik perairan pantai Pulau Manado Tua tergolong normal untuk kegiatan budidaya matrikultur. Secara geografi Pulau terletak pada koordinat 01Âº 37â€™ 57â€ LU dan 124Âº 41â€™ 56â€ BT. Pada lokasi I yang sangat sesuai seluas 44,03 m2, sedangkan lahan yang sesuai seluas 34,25 m2 dan lahan yang sesuai bersyarat seluas 17,13 m2.Â  Untuk lokasi IIÂ  areal yang sangat memenuhi syarat adalah seluas 70.50 m2, dan yang memenuhi syarat sesuai adalah seluas 49,86 m2, dan yang memenuhi sesuai bersyarat seluas 27,51 m2. Luas daratan Pulau Manado Tua 1.056,02 ha . Kondisi sumber air tawar di belum berpotensi untuk memenuhi kebutuhan masyarakat dan wisatawan yang berkunjung.Kata kunci: kesesuaian lahan, budidaya perikanan, pemanfaatan air tawar, Pulau Manado Tua